ADAPTOR PROTEINS ACTIVATE FIBROBLASTS IN SYSTEMIC SCLEROSIS - Ariza, Y.; Weber, Stefanie; Neise, N.; Kreuter, A.; Schett, Georg; Distler, Jörg; Ramming, Andreas (ANNALS OF THE RHEUMATIC DISEASES, 2020)
CRIS-Team WoS Importer:2020-08-21

Cutting Edge: Homeostasis of Innate Lymphoid Cells Is Imbalanced in Psoriatic Arthritis - Soare, Alina; Weber, Stefanie; Maul, Lisa; Rauber, Simon; Gheorghiu, Ana Maria; Luber, Markus; Houssni, Ismail; Kleyer, Arnd; von Pickardt, Gero; Gado, Manuel; Simon, David; Rech, Jürgen; et al. (Journal of Immunology, 2018)
Innate lymphoid cells (ILC) have a high potency for cytokine production independent of specific Ag stimulation. Imbalance of ILC subsets may influence cytokine production in humans and hence be associated with the development of inflammatory disease. Evidence for an imbalance of ILC homeostasis in human disease, however, is very limited to date. In this study we show that psoriatic arthritis (PsA), a severe disease of the joints depending on the activation of the IL-23/IL-17 pathway, is characterized by a skewed ILC homeostasis. Circulating ILC3s as potent source of IL-17/IL-22 were elevated in active PsA, whereas ILC2s, which produce proresolving cytokines, were decreased. The ILC2/ILC3 ratio was significantly correlated with clinical disease activity scores and the presence of imaging signs of joint inflammation and bone damage. Multivariable analysis showed that a high ILC2/ILC3 ratio is associated with remission in PsA, suggesting that specific alterations of ILC homeostasis control disease activity in PsA.
EVALuna2:13524

Destabilization of the human epigenome: consequences of foreign DNA insertions - Weber, Stefanie; Hofmann, Andrea; Herms, Stefan; Hoffmann, Per; Dörfler, Walter (Epigenomics, 2015)
We previously reported changes of DNA methylation and transcription patterns in mammalian cells that carry integrated foreign DNA. Experiments were now designed to assess the epigenetic consequences of inserting a 5.6 kbp plasmid into the human genome.Differential transcription and CpG methylation patterns were compared between transgenomic and nontransgenomic cell clones by using gene chip microarray systems.In 4.7% of the 28.869 gene segments analyzed, transcriptional activities were up- or downregulated in the transgenomic cell clones. Genome-wide profiling revealed differential methylation in 3791 of > 480,000 CpG's examined in transgenomic versus nontransgenomic clones.The data document genome-wide effects of foreign DNA insertions on the epigenetic stability of human cells. Many fields in experimental biology and medicine employ transgenomic or otherwise genome-manipulated cells or organisms without considering the epigenetic consequences for the recipient genomes.
EVALuna2:8268

DNA methylation and transcription in HERV (K, W, E) and LINE sequences remain unchanged upon foreign DNA insertions - Weber, Stefanie; Jung, Susan; Dörfler, Walter (Epigenomics, 2016)
DNA methylation and transcriptional profiles were determined in the regulatory sequences of the human endogenous retroviral (HERV-K, -W, -E) and LINE-1.2 elements and were compared between non-transgenomic and plasmid-transgenomic cells.DNA methylation profiles in the HERV (K, W, E) and LINE sequences were determined by bisulfite genomic sequencing. The transcription of these genome segments was assessed by quantitative real-time PCR.In HERV-K, HERV-W and LINE-1.2 the levels of DNA methylation ranged between 75 and 98%, while in HERV-E they were around 60%. Nevertheless, the HERV and LINE-1.2 sequences were actively transcribed. No differences were found in comparisons of HERV and LINE-1.2 CpG methylation and transcription patterns between non-transgenomic and plasmid-transgenomic HCT116 cells.The insertion of a 5.6 kbp plasmid into the HCT116 genome had no effect on the HERV and LINE-1.2 methylation and transcription profiles, although other parts of the HCT116 genome had shown marked changes. These repetitive sequences are transcribed, probably because the large number of HERV and LINE-1.2 elements harbor copies with non- or hypo-methylated long terminal repeat sequences.
EVALuna2:8330

Epigenetic analysis of HIV-1 proviral genomes from infected individuals: predominance of unmethylated CpG's - Weber, Stefanie; Weiser, Barbara; Kemal, Kimdar S.; Burger, Harold; Ramirez, Christina M.; Korn, Klaus; Anastos, Kathryn; Kaul, Rupert; Kovacs, Colin; Dörfler, Walter (Virology, 2014)
Efforts to cure HIV-1 infections aim at eliminating proviral DNA. Integrated DNA from various viruses often becomes methylated de novo and transcriptionally inactivated. We therefore investigated CpG methylation profiles of 55 of 94 CpG's (58.5%) in HIV-1 proviral genomes including ten CpG's in each LTR and additional CpG's in portions of gag, env, nef, rev, and tat genes. We analyzed 33 DNA samples from PBMC's of 23 subjects representing a broad spectrum of HIV-1 disease. In 22 of 23 HIV-1-infected individuals, there were only unmethylated CpG's regardless of infection status. In one long term nonprogressor, however, methylation of proviral DNA varied between 0 and 75% over an 11-year period although the CD4+ counts remained stable. Hence levels of proviral DNA methylation can fluctuate. The preponderance of unmethylated CpG's suggests that proviral methylation is not a major factor in regulating HIV-1 proviral activity in PBMC's. Unmethylated CpG's may play a role in HIV-1 immunopathogenesis.
EVALuna2:8239

HIGH DIMENSIONAL ANALYSIS REVEAL A NETWORK OF CERTAIN TRANSCRIPTION FACTORS THAT LINK VASCULOPATHY AND ORGAN FIBROSIS IN SYSTEMIC SCLEROSIS - Anchang, Charles Gwellem; Lawaree, B. Matalobos; Weber, Stefanie; Rauber, S.; Wohlfahrt, T.; Luber, M.; Kreuter, A.; Schett, Georg; Distler, Jörg; Ramming, A. (ANNALS OF THE RHEUMATIC DISEASES, 2020)
CRIS-Team WoS Importer:2020-08-21

IL-9-Producing Innate Lymphoid Cells - Keyplayers That Orchestrate Resolution of Chronic Inflammation in Arthritis - Rauber, Simon; Luber, Markus; Weber, Stefanie; Maul, Lisa; Soare, Alina; Wohlfahrt, Thomas; Bozec, Aline; Herrmann, Martin; Zaiss, Mario; Fearon, Ursula; Veale, Douglas J.; Canete, Juan; et al. (2017)
EVALuna2:33440

INNATE LYMPHOID CELLS ARE PREDICTORS OF DISEASE PROGRESSION IN SYSTEMIC SCLEROSIS: A 3-YEARS FOLLOW-UP STUDY - Soare, A.; Weber, Stefanie; Schett, Georg; Distler, Jörg; Ramming, Andreas (ANNALS OF THE RHEUMATIC DISEASES, 2020)
CRIS-Team WoS Importer:2020-08-21

INNATE LYMPHOID CELLS CORRELATE WITH DISEASE ACTIVITY AND BONE REMODELLING IN PSORIATIC ARTHRITIS - Soare, A.; Weber, Stefanie; Maul, L.; Rauber, Simon; Gheorghiu, A. M.; Houssni, I.; Kleyer, Arnd; Luber, M.; Rech, Jürgen; Schett, Georg; Distler, Jörg; Ramming, A. (2018)
EVALuna2:34985

INNATE LYMPHOID CELLS INDUCE A FIBROTIC PHENOTYPE OF FIBROBLASTS - Weber, Stefanie; Anchang, Charles Gwellem; Rauber, S.; Luber, M.; Raimondo, M. G.; Ariza, Y.; Rigau, A. Rius; Kreuter, A.; Schett, Georg; Distler, Jörg; Ramming, A. (ANNALS OF THE RHEUMATIC DISEASES, 2020)
CRIS-Team WoS Importer:2020-08-21

Innate Lymphoid Cells - New Players in Psoriatic Arthritis - Soare, Alina; Weber, Stefanie; Maul, Lisa; Gheorghiu, Ana Maria; Housni, Ismail; Kleyer, Arnd; Luber, Markus; Rauber, Simon; Simon, David; Rech, Jürgen; Schett, Georg; Distler, Jörg; et al. (2017)
EVALuna2:33444

Intracellular African swine fever virus DNA remains unmethylated in infected Vero cells - Weber, Stefanie; Hakobyan, Astghik; Zakaryan, Hovakim; Dörfler, Walter (Epigenomics, 2018)
Aim: Sequence-specific CpG methylation of eukaryotic promoters is an important epigenetic signal for long-term gene silencing. We have now studied the methylation status of African swine fever virus (ASFV) DNA at various times after infection of Vero cells in culture. Methods & results: ASFV DNA was detectable throughout the infection cycle and was found unmethylated in productively infected Vero cells as documented by bisulfite sequencing of 13 viral DNA segments. Conclusion: ASFV DNA does not become de novo methylated in the course of infection in selected segments spread across the entire genome. Thus DNA methylation does not interfere with ASFV genome transcription. Lack of de novo methylation has previously been observed for free intracellular viral DNA in cells permissively infected with human adenoviruses, with human papillomaviruses and others.
EVALuna2:35287

PU.1 controls fibroblast polarization and tissue fibrosis - Wohlfahrt, Thomas; Rauber, Simon; Uebe, Steffen; Luber, Markus; Soare, Alina; Ekici, Arif Bülent; Weber, Stefanie; Matei, Alexandru-Emil; Chen, Chih-Wei; Maier, Christiane; Karouzakis, Emmanuel; Kiener, Hans P.; et al. (Nature, 2019)
Fibroblasts are polymorphic cells with pleiotropic roles in organ morphogenesis, tissue homeostasis and immune responses. In fibrotic diseases, fibroblasts synthesize abundant amounts of extracellular matrix, which induces scarring and organ failure. By contrast, a hallmark feature of fibroblasts in arthritis is degradation of the extracellular matrix because of the release of metalloproteinases and degrading enzymes, and subsequent tissue destruction. The mechanisms that drive these functionally opposing pro-fibrotic and pro-inflammatory phenotypes of fibroblasts remain unknown. Here we identify the transcription factor PU.1 as an essential regulator of the pro-fibrotic gene expression program. The interplay between transcriptional and post-transcriptional mechanisms that normally control the expression of PU.1 expression is perturbed in various fibrotic diseases, resulting in the upregulation of PU.1, induction of fibrosis-associated gene sets and a phenotypic switch in extracellular matrix-producing pro-fibrotic fibroblasts. By contrast, pharmacological and genetic inactivation of PU.1 disrupts the fibrotic network and enables reprogramming of fibrotic fibroblasts into resting fibroblasts, leading to regression of fibrosis in several organs.
EVALuna2:35476

PU.1 INHIBITOR DB1976 CONTROLS FIBROBLAST POLARIZATION IN SYSTEMIC SCLEROSISAND LEADS TO REGRESSION OF FIBROSIS IN DIFFERENT MODELS OF ORGAN FIBROSIS - Wohlfahrt, Thomas; Rauber, Simon; Luber, Markus; Soare, Alina; Weber, Stefanie; Matei, Alexandru-Emil; Chen, Chih-Wei; Karouzakis, Emmanuel; Kiener, Hans; Pachera, Elena; Dees, Clara; Kreuter, Alexander; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2019)
CRIS-Team WoS Importer:2019-07-12

Resolution of inflammation by interleukin-9-producing type 2 innate lymphoid cells - Rauber, Simon; Luber, Markus; Weber, Stefanie; Maul, Lisa; Soare, Alina; Wohlfahrt, Thomas; Lin, Neng-Yu; Dietel, Katharina; Bozec, Aline; Herrmann, Martin; Kaplan, Mark H.; Weigmann, Benno; et al. (Nature Medicine, 2017)
Inflammatory diseases such as arthritis are chronic conditions that fail to resolve spontaneously. While the cytokine and cellular pathways triggering arthritis are well defined, those responsible for the resolution of inflammation are incompletely characterized. Here we identified interleukin (IL)-9-producing type 2 innate lymphoid cells (ILC2s) as the mediators of a molecular and cellular pathway that orchestrates the resolution of chronic inflammation. In mice, the absence of IL-9 impaired ILC2 proliferation and activation of regulatory T (Treg) cells, and resulted in chronic arthritis with excessive cartilage destruction and bone loss. In contrast, treatment with IL-9 promoted ILC2-dependent Treg activation and effectively induced resolution of inflammation and protection of bone. Patients with rheumatoid arthritis in remission exhibited high numbers of IL-9(+) ILC2s in joints and the circulation. Hence, fostering IL-9-mediated ILC2 activation may offer a novel therapeutic approach inducing resolution of inflammation rather than suppression of inflammatory responses.
EVALuna2:13255

Review - EPIGENETICS, 2018 Inheritable Epigenetic Response towards Foreign DNA Entry by Mammalian Host Cells: A Guardian of Genomic Stability - Dörfler, Walter; Weber, Stefanie; Naumann, Anja (Epigenetics, 2018)
Apart from its well-documented role in long-term promoter silencing, the genome-wide distribution patterns of 28 million methylated or unmethylated CpG dinucleotides, e. g. in the human genome, is in search of genetic functions. We have set out to study changes in the cellular CpG methylation profile upon introducing foreign DNA into mammalian cells. As stress factors served the genomic integration of foreign (viral or bacterial plasmid) DNA, virus infections or the immortalization of cells with Epstein Barr Virus (EBV). In all instances investigated, alterations in cellular CpG methylation and transcription profiles were observed to different degrees. In the case of adenovirus DNA integration in adenovirus type 12 (Ad12)-transformed hamster cells, the extensive changes in cellular CpG methylation persisted even after the complete loss of all transgenomic Ad12 DNA. Hence, stress-induced alterations in CpG methylation can be inherited independent of the continued presence of the transgenome. Upon virus infections, changes in cellular CpG methylation appear early after infection. In EBV immortalized as compared to control cells, CpG hypermethylation in the far-upstream region of the human FMR1 promoter decreased four-fold. We conclude that in the wake of cellular stress due to foreign DNA entry, preexisting CpG methylation patterns were altered, possibly at specific CpG dinucleotides. Frequently, transcription patterns were also affected. As a working concept, we view CpG methylation profiles in mammalian genomes as a guarding sensor for genomic stability under epigenetic control. As a caveat towards manipulations of cells with foreign DNA, such cells can no longer be considered identical to their un-manipulated counterparts.
EVALuna2:35356

SARS-CoV-2 worldwide replication drives rapid rise and selection of mutations across the viral genome: a time-course study – potential challenge for vaccines and therapies - Weber, Stefanie; Ramirez, Christina M.; Weiser, Barbara; Burger, Harold; Dörfler, Walter (Embo Molecular Medicine, 2021)
Scientists and the public were alarmed at the first large viral variant of SARS-CoV-2 reported in December 2020. We have followed the time course of emerging viral mutants and variants during the SARS-CoV-2 pandemic in ten countries on four continents. We examined > 383,500 complete SARS-CoV-2 nucleotide sequences in GISAID (Global Initiative of Sharing All Influenza Data) with sampling dates extending until April 05, 2021. These sequences originated from ten different countries: United Kingdom, South Africa, Brazil, United States, India, Russia, France, Spain, Germany, and China. Among the 77 to 100 novel mutations, some previously reported mutations waned and some of them increased in prevalence over time. VUI2012/01 (B.1.1.7) and 501Y.V2 (B.1.351), the so-called UK and South Africa variants, respectively, and two variants from Brazil, 484K.V2, now called P.1 and P.2, increased in prevalence. Despite lockdowns, worldwide active replication in genetically and socio-economically diverse populations facilitated selection of new mutations. The data on mutant and variant SARS-CoV-2 strains provided here comprise a global resource for easy access to the myriad mutations and variants detected to date globally. Rapidly evolving new variant and mutant strains might give rise to escape variants, capable of limiting the efficacy of vaccines, therapies, and diagnostic tests.
CRIS-Team Scopus Importer:2021-06-11
Keywords: high incidence of C to T transitions; numerous new mutations; South African and Brazil variants; time course of SARS-CoV-2 mutant emergence; UK variant B.1.1.7

Signal hotspot mutations in SARS-CoV-2 genomes evolve as the virus spreads and actively replicates in different parts of the world - Weber, Stefanie; Ramirez, Christina; Dörfler, Walter (Virus Research, 2020)
Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) was first identified in Wuhan, China late in 2019. Nine months later (Sept. 23, 2020), the virus has infected > 31.6 million people around the world and caused > 971.000 (3.07 %) fatalities in 220 countries and territories. Research on the genetics of the SARS-CoV-2 genome, its mutants and their penetrance can aid future defense strategies. By analyzing sequence data deposited between December 2019 and end of May 2020, we have compared nucleotide sequences of 570 SARS-CoV-2 genomes from China, Europe, the US, and India to the sequence of the Wuhan isolate. During worldwide spreading among human populations, at least 10 distinct hotspot mutations had been selected and found in up to > 80 % of viral genomes. Many of these mutations led to amino acid exchanges in replication-relevant viral proteins. Mutations in the SARS-CoV-2 genome would also impinge upon the secondary structure of the viral RNA molecule and its repertoire of interactions with essential cellular and viral proteins. The increasing frequency of SARS-CoV-2 mutation hotspots might select for dangerous viral pathogens. Alternatively, in a 29.900 nucleotide-genome, there might be a limit to the number of mutable and selectable sites which, when exhausted, could prove disadvantageous to viral survival. The speed, at which novel SARS-CoV-2 mutants are selected and dispersed around the world, could pose problems for the development of vaccines and therapeutics.
CRIS-Team Scopus Importer:2020-10-09
Keywords: Consequences for secondary and tertiary structures of viral RNA; Impact on replication-relevant viral proteins; Questions about immunogenesis and vaccine development; Selection of viral hotspot mutations; Sequence comparisons between 570 viral genomes to Wuhan isolate; Severe acute respiratory syndrome Coronavirus-2 (SARS-CoV-2)

Type 2 innate lymphoid cell counts are increased in patients with systemic sclerosis and correlate with the extent of fibrosis - Wohlfahrt, Thomas; Usherenko, Svetlana; Englbrecht, Matthias; Dees, Clara; Weber, Stefanie; Beyer, Christian; Gelse, Kolja; Distler, Oliver; Schett, Georg; Distler, Jörg; Ramming, Andreas (Annals of the Rheumatic Diseases, 2016)
Objective Type 2 innate lymphoid cells (ILC2s), a recently identified population of lymphoid cells lacking lineage-specific receptors, promote type 2 immunity and tissue remodelling. However, the contributive role of ILC2s in the pathogenesis of systemic sclerosis (SSc) is unknown. We aimed to evaluate the levels and correlations with fibrotic manifestations in SSc. Methods 69 patients with SSc and 47 healthy controls were included. Blood samples and skin sections were analysed by flow cytometry and immunohistochemically by staining two complementary panels of markers. Results Dermal and circulating ILC2s were significantly elevated in patients with SSc compared with controls. Dermal, but not circulating ILC2s were activated. Stratification of the SSc population in patients with limited cutaneous SSc (lcSSc) and diffuse cutaneous SSc (dcSSc) demonstrated increased levels of ILC2s in both subgroups with significantly higher frequencies in dcSSc compared with lcSSc. Moreover, dermal and circulating ILC2 counts correlated closely with the modified Rodnan skin score and with the presence of pulmonary fibrosis. Conclusions ILC2 counts are elevated in patients with SSc and correlate with the extent of skin fibrosis and the presence of interstitial lung disease providing compelling evidence for profibrotic effect of ILC2s in SSc.
EVALuna2:13149

TYPE 2 INNATE LYMPHOID CELLS ARE RAPIDLY AND PERSISTENTLY RECRUITED IN EXPERIMENTAL FIBROSIS AND THEIR COUNTS CORRELATE WITH THE SEVERITY OF SKIN AND LUNG FIBROSIS IN SYSTEMIC SCLEROSIS - Wohlfahrt, T.; Weber, Stefanie; Englbrecht, Matthias; Dees, Clara; Beyer, Christian; Distler, O.; Schett, Georg; Distler, Jörg; Ramming, A. (2016)
EVALuna2:13485

Type 2 Innate Lymphoid Cells - Cellular Source of Profibrotic Mediators Rapidly and Persistently Recruited in Experimental Fibrosis and Systemic Sclerosis - Weber, Stefanie; Wohlfahrt, Thomas; Rauber, Simon; Luber, Markus; Englbrecht, Matthias; Dees, Clara; Beyer, Christian; Distler, Oliver; Schett, Georg; Distler, Jörg; Ramming, Andreas (2016)
EVALuna2:35067

TYPE 3 INNATE LYMPHOID CELLS ARE KEY DRIVERS OF PSORIATIC ARTHRITIS - Raimondo, M. G.; Rauber, S.; Luber, M.; Rigau, A. Rius; Weber, Stefanie; Anchang, Charles Gwellem; Agarwal, Rahul; Soare, A.; Sticherling, Michael; Rech, Jürgen; Kleyer, Arnd; Distler, Jörg; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2020)
CRIS-Team WoS Importer:2020-08-21

Ubiquitous Micro-Modular Homologies among Genomes from Viruses to Bacteria to Human Mitochondrial DNA: Platforms for Recombination during Evolution? - Weber, Stefanie; Ramirez, Christina M.; Dörfler, Walter (Viruses, 2022)
The emerging Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) and its variants have raised tantalizing questions about evolutionary mechanisms that continue to shape biology today. We have compared the nucleotide sequence of SARS-CoV-2 RNA to that of genomes of many different viruses, of endosymbiotic proteobacterial and bacterial DNAs, and of human mitochondrial DNA. The entire 4,641,652 nt DNA sequence of Escherichia coli K12 has been computer-matched to SARS-CoV-2 RNA. Numerous, very similar micro-modular clusters of 3 to 13 nucleotides lengths were detected with sequence identities of 40 to >50% in specific genome segments between SARS-CoV-2 and the investigated genomes. These clusters were part of patch-type homologies. Control sequence comparisons between 1000 randomly computer-composed sequences of 29.9 kb and with the A, C, G, T base composition of SARS-CoV-2 genome versus the reference Wuhan SARS-CoV-2 sequence showed similar patterns of sequence homologies. The universal A, C, G, T genetic coding mode might have succeeded in evolution due in part to its built-in capacity to select for a substantial reservoir of micro-modular domains and employ them as platforms for integrative recombination. Their role in SARS-CoV-2 interspecies transition and the generation of variants appears likely, but their actual involvement will require detailed investigations.
CRIS-Team Scopus Importer:2022-05-13
Keywords: Four letter genetic encoding system; Micro-modular identities in 1000 randomized SARS-CoV-2 genomes; Micro-modular sequence identities; Patch type sequence similarities; SARS-CoV-2 RNA compared to genomes of many viruses; protobacteria; Escherichia coli; Signals for evolution; annealing and integrative recombination; The 4; 641; 652 nt DNA sequence of Escherichia coli K12